Pendampingan Penyusunan Bahan Ajar Berbasis Microlearning Guna Memfasilitasi Kemerdekaan Belajar Siswa - Purwana, Dedi; Effendi, Mohammad Sofwan; Adha, Maulana Amirul; Andini, Fatma Ari; Ma’ruf, Muhammad Raihan Nur; Azzahro, Hilmun (Lembaga Dongan Dosen, 2024)
The Freedom to learn policy encourages improving the quality of education through adaptive and innovative learning. This community service program aims to improve the skills of teachers at SMPN 2 Curugbitung in compiling microlearning-based teaching materials that can facilitate students' learning independence. The method in this program includes several stages, starting from socialization, training, technology implementation, mentoring, to evaluation and sustainability plans. Teachers are trained in the use of technology to produce more interactive and interesting microlearning-based teaching materials. Evaluation through pre-tests and post-tests showed a significant increase in skills after mentoring, where teachers were able to develop adaptive teaching materials that are in accordance with the diverse needs of students. This microlearning approach provides flexibility in teaching and supports the freedom to learn policy. The results of this program confirm that microlearning can be a solution to improve the quality of learning in schools.